Phototransduction in a Transgenic Mouse Model of Nougaret Night Blindness - Moussaif, Mustapha (J Neurosci, 2006)
The Nougaret form of dominant stationary night blindness is linked to a G38D mutation in the rod transducin-α subunit (Tα). In this study, we have examined the mechanism of Nougaret night blindness using transgenic mice expressing TαG38D. The biochemical, electrophysiological, and vision-dependent behavioral analyses of the mouse model revealed a unique phenotype of reduced rod sensitivity, impaired activation, and slowed recovery of the phototransduction cascade. Two key deficiencies in TαG38D function, its poor ability to activate PDE6 (cGMP phosphodiesterase) and decreased GTPase activity, are found to be the major mechanisms altering visual signaling in transgenic mice. Despite these defects, rod-mediated sensitivity in heterozygous mice is not decreased to the extent seen in heterozygous Nougaret patients.